2009
DOI: 10.1097/dad.0b013e31819d764d
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Features in Both the Eschar and Erythematous Lesions of Tsutsugamushi Disease: Identification of CD30+ Cell Infiltration in Tsutsugamushi Disease

Abstract: Tsutsugamushi disease is an acute febrile infectious disease caused by Rickettsia tsutsugamushi. An infection is heralded by the presence of an eschar at the site of the inoculating chigger bite and followed by the development of a disseminated erythematous macular rash. CD30 expression is found in anaplastic large cell lymphoma; however, expression in nonneoplastic cutaneous disorders, such as atopic dermatitis, drug reactions, scabies, and various infectious diseases, has also been reported. Study of the cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The basic histopathologic findings reveal multiplication of O. tsutsugamushi in the endothelial cells lining the small blood vessels, perivasculitis and focal interstitial mononuclear cell infiltrations, and edema. Perivasculitis may involve the lung, heart, brain, kidneys, gastrointestinal tract, liver, spleen, and lymph node [73].…”
Section: Clinical Features and Pathogenesismentioning
confidence: 99%
“…The basic histopathologic findings reveal multiplication of O. tsutsugamushi in the endothelial cells lining the small blood vessels, perivasculitis and focal interstitial mononuclear cell infiltrations, and edema. Perivasculitis may involve the lung, heart, brain, kidneys, gastrointestinal tract, liver, spleen, and lymph node [73].…”
Section: Clinical Features and Pathogenesismentioning
confidence: 99%
“…Histopathological studies of eschars in humans [14][18] and cynomolgus monkeys [19] have described perivascular collections of mononuclear cells, including lymphocytes, plasma cells and macrophages. In recent studies, immunophenotyping revealed a dominance of CD3+ T-cells and CD68+ monocyte/macrophages within infiltrates [15] and an association of O. tsutsugamushi with the epithelial lining covering the surface of the sweat ducts and glands [14]. Eschars can have high bacterial loads and have been shown to be useful specimens for both PCR-based and immunohistochemical diagnosis [14], [20].…”
Section: Introductionmentioning
confidence: 99%
“…Clues of those effects could be obtained from the study of eschars from human cases. Indeed, a recent study of 11 eschars from patients with confirmed scrub typhus confirmed the classic histological finding of epidermal necrosis and ulceration accompanied by significant neutrophilic infiltration adjacent to the area of necrosis and mononuclear cell infiltrates in the dermis (Lee et al, 2009; Paris et al, 2012). Those infiltrates consisted of T cells, monocytes, and dermal dendritic cells.…”
Section: Effect Of the Vectormentioning
confidence: 69%